Patterns of hybrid seed inviability in the Mimulus guttatus sp. complex reveal a potential role of parental conflict in reproductive isolation - Coughlan, Jenn M. (Curr Biol, 2019)
Genomic conflicts may play a central role in the evolution of reproductive barriers. Theory predicts that early-onset hybrid inviability may stem from conflict between parents for resource allocation to offspring. Here we describe M. decorus; a group of cryptic species within the M. guttatus species complex that are largely reproductively isolated by hybrid seed inviability (HSI). HSI between M. guttatus and M. decorus is common and strong, but populations of M. decorus vary in the magnitude and directionality of HSI with M. guttatus. Patterns of HSI between M. guttatus and M. decorus, as well as within M. decorus conform to the predictions of parental conflict: firstly, reciprocal F1s exhibit size differences and parent-of-origin specific endosperm defects, secondly the extent of asymmetry between reciprocal F1 seed size is correlated with asymmetry in HSI, and lastly, inferred differences in the extent of conflict predict the extent of HSI between populations. We also find that HSI is rapidly evolving, as populations that exhibit the most HSI are each others’ closest relative. Lastly, while all populations appear largely outcrossing, we find that the differences in the inferred strength of conflict scale positively with π, suggesting that demographic or life history factors other than transitions to self-fertilization may influence the rate of parental conflict driven evolution. Overall, these patterns suggest the rapid evolution of parent-of-origin specific resource allocation alleles coincident with HSI within and between M. guttatus and M. decorus. Parental conflict may therefore be an important evolutionary driver of reproductive isolation.